Predictors of spontaneous abortion among reproductive-aged women at tertiary level hospital, Kathmandu - Pun, Khagi Maya; Silwal, Kalpana; Poudel, Ambika; Panthee, Bimala (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Spontaneous abortion (SA) is one of the adverse outcomes during pregnancy, which is a challenge for maternal well-being. The present study aimed to analyze the predictors of SA among reproductive age women.Method: A hospital-based case-control study was conducted at Patan hospital, Nepal. The consecutive sampling technique was used to select the cases (84) and a purposive sampling technique was used for controls (168) in a 1:2 ratio. Ethical approval was obtained. Data were collected through face to face interviews using a structured questionnaire. Descriptive and inferential statistics (Chi-square, Fisher exact test, and logistic regression) were used for analyzing the data.Result: We found that previous history of abortion (OR=3.80, 95% CI=1.8-7.70), heavy lifting (OR=20.45, 95% CI =4.48-93.38), emotional disturbance (OR=10.06, 95% CI=1.06-96.96), health problems (fever of unknown cause and urinary tract infection) during pregnancy (OR=16.53, 95% CI=1.90-143.41), coffee intake (OR=0.36, 95% CI=0.20-0.63), unplanned pregnancy (OR=0.10,95% CI=0.04-0.22), preconception counseling/care not received (OR=6.48, 95% CI=2.18-19.21) were the significant predictors of SA among reproductive age women.Conclusion: Our findings show that the previous history of abortion, heavy lifting, emotional disturbances, health problems, and coffee intake during pregnancy are the significant cause of SA; and preconception counseling and planned pregnancy are protective factors.